Amphibian predation by Lyroderma lyra (Family: Megadermatidae) in Bangladesh highlights an expanded trophic role (Journal of Bangladesh Academy of Sciences, 2025)
We documented amphibian predation by the greater false vampire bat (Lyroderma lyra) in Bangladesh, expanding current knowledge of its trophic ecology. This observation highlights the ecological role of this species as both an insectivore and a carnivore, and underscores the need to investigate the frequency and ecological drivers of such predatory behavior.J. Bangladesh Acad. Sci. 49(2); 299-301: December 2025